2017
DOI: 10.1002/brb3.847
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of carotid plaque and carotid common artery intima‐media thickening in a high‐stroke‐risk population

Abstract: IntroductionTo analyze the risk factors of carotid plaque (CP) and carotid common artery intima‐media thickening (CCAIMT) and the association between the risk factors and CP numbers and the side of the CCAIMT in a high‐stroke‐risk population.MethodsCarotid ultrasonography was conducted in 2025 participants with high stroke risk. Participants were divided into different groups according to the results of the ultrasound. The risk factors and blood biochemical indices were recorded.ResultsThe presence of CP and C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 29 publications
6
14
0
Order By: Relevance
“…In this study, we found that the association of hypertension with the presence of CP and multiple CPs, which was consistent with previous studies [18,19]. Previous studies have shown that hypertension may be the most prominent risk factor for carotid atherosclerosis [22,23].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In this study, we found that the association of hypertension with the presence of CP and multiple CPs, which was consistent with previous studies [18,19]. Previous studies have shown that hypertension may be the most prominent risk factor for carotid atherosclerosis [22,23].…”
Section: Discussionsupporting
confidence: 93%
“…This study found that DM was associated with the presence of CP and multiple CPs, which was consistent with previous studies [3,18,19]. The underlying mechanisms of the correlation between diabetes and carotid atherosclerosis may be explained by the decrease in the bioavailability of the main anti-atherosclerotic factor endothelium-derived nitric oxide [20], and abnormal platelet activity caused by insulin insu cient and/or resistance [21].…”
Section: Discussionsupporting
confidence: 91%
“…Results also showed that Jilin had the highest rate of CAS, while Xinjiang had the lowest one, which may be due to the differences in sample areas and populations. As for the prevalence of carotid plaques, IMT, and stenosis, it varies widely (14,19). Our data show that the prevalence of IMT, plaque, and stenosis were 39.22, 41.25, and 4.05%, respectively.…”
Section: Discussionmentioning
confidence: 64%
“…The common risks for CAS in both urban and rural groups reported in our study were consistent with numerous previous studies. For example, risk factors for carotid plaque and IMT include age, sex, smoking, diabetes, hypertension, high FBG and LDL levels, decreased HDL-C levels, and history of stroke (19,20).…”
Section: Discussionmentioning
confidence: 99%
“…Although a significant association between increased baseline cIMT and first‐ever carotid plaque has been obtained, this does not necessarily imply a direct relationship between them. Elevated cIMT and carotid plaque have both been associated with a number of cardiovascular risk factors and also share a considerable amount of these risk factors. Hence, the possibility of a confounding factor driving the current result towards positivity exists.…”
Section: Discussionmentioning
confidence: 99%